Evaluating the Neurological Outcomes after Gamma Knife Radiosurgery for Symptomatic Skull Base Meningiomas Based on Their Locations: Single Institution Experience - Kazemi, Farid; Javadnia, Parisa; Tabibkhooei, Alireza; Naghshbandi, Mobin; kalkhaje, Vahid Ghorbani (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Background: Meningioma is the most common primary benign intracranial tumor. Gross total resection of skull base meningioma (SBM) is so challenging due to its relevant high morbidity. Gamma knife radiosurgery is concerned, by providing a favorable therapeutic option in the management of SBM. Aim: This study aims to evaluate the neurological outcome after GKRS as an adjuvant or primary treatment for SBM according to their locations. Methods: This retrospective cross-sectional study consisted of 108 patients with SBM who underwent GKRS as an adjuvant or primary treatment. Patient’s medical records were collected to assess their demographic characteristics, clinical presentation, and clinical evaluations in follow-up visits. We found 40 patients with cavernous sinus meningioma (CSM), 36 patients with petroclival meningioma (PCM), and 22 patients with cerebellopontine angle meningioma (CPM). Of these, 81.1% were female (n = 90) with a median age of 52.68 years. Statistical analysis was performed using the chi-square test to evaluate the relationship between the duration of symptoms, age, gender, modality of GKRS (fractionated or not fractionated), and tumor size change on the likelihood of improvement and deterioration of neurological symptoms. The mean tumor volume was 4.5 cm3 and the mean marginal dose was 13 Gy. Results: Tumor control was achieved in 96.4% of patients at a median follow-up of 38.4 months. Overall, 17 of 108 patients (15.6%) report improvement in their neurological symptoms. The majority of neurological symptoms were related to tumors which were located in the cavernous sinus 36%, Petroclival region 32.4%, and CPA 19.8%, respectively. Patients with CPM demonstrated lower rates of neurological symptom improvement compared to patients with PCM and CSM. Deterioration of neurological symptoms after GKRS developed in 11 patients (10.1%) which was more reported by patients with CSM than the others. The most improvement in cranial nerve deficit was in CN VI, V, and VIII among patients with CSM, PCM, and CPM respectively. Conclusion: GKRS is acceptable as a primary or adjuvant treatment for SBM by providing an appreciable rate of improvement in neurological symptoms.